PENDIDIKAN BERBASIS KEARIFAN LOKAL DI ABAD 21 - Didin Wahidin (UJMES (Uninus Journal of Mathematics Education and Science), 2020)
Human progress is increasingly developing due to the increasingly advanced science and technology in the 21st century, also develops aparadigm of human thinking that is increasingly diverse. This also results in increasingly large challenges in the world of educationtoday. Therefore, everything must be prepared relating to education in the 21st century that changes and develops rapidly along with therapid development of Science and technology. The rapid changes that occur in the world of education are expected to not cause us to beuprooted from the cultural roots that we have inherited from time to time. Based on such background, an education based on localwisdom should be developed. Local wisdom, among others, in the form of values, norms, beliefs, natural resources, culture and customs,or rules that support the development of human resources. Local wisdom is integrated into various educational activities both curricular,co-curricular and extra-curricular as well as school or educational institution management. The learning can be done by choosingstrategies, approaches, methods and techniques that are considered suitable for incorporating local wisdom in various forms.